Ovariectomized rat model and shape variation in the bony labyrinth. Issue 11 (9th February 2022) - Ward, Devin L.; Schroeder, Lauren; Tinius, Alexander; Niccoli, Sarah; Voth, Riley; Lees, Simon J.; Silcox, Mary; Viola, Bence; Sanzo, Paolo
Abstract: Postmenopausal osteoporosis is a serious concern in aging individuals, but has not been explored for its potential to alter the shape of the inner ear by way of increased remodeling in the otic capsule. The otic capsule, or bony labyrinth, is thought to experience uniquely limited remodeling after development due to high levels of osteoprotegerin. On this basis, despite the widespread remodeling that accompanies osteoporosis, we hypothesize that both the shape and volume of the semicircular canals will resist such changes. To test this hypothesis, we conducted three‐dimensional geometric morphometric shape analysis on microcomputed tomographic data collected on the semicircular canals of an ovariectomized (OVX) rat model. A Procrustes ANOVA found no statistically significant differences in shape between surgery and sham groups, and morphological disparity testing likewise found no differences in shape variation. Univariate testing found no differences in semicircular volume between OVX and control groups. The range of variation in the OVX group, however, is greater than in the sham group but this difference does not reach statistical significance, perhaps because of a combination of small effect size and low sample size. This finding suggests that labyrinthine shape remains a tool for assessing phylogeny and function in the fossil record, but that it is possible that osteoporosis may be contributing to intraspecific shape variation in the bony labyrinth. This effect warrants further exploration at a microstructural level with continued focus on variables related to remodeling.